Research in action: assessment and treatment of child sexual abusers - Chaffin, Mark (Journal of interpersonal violence, 1994)
Selected recent studies on child sexual abusers and abuser treatment are reviewed from the perspective of their implications for patient assessment and treatment. Emphasis is placed on the settings in which studies are conducted and the corresponding treatment settings to which they might be generalized. It is suggested that clinicians be aware of the vast diversity in the abuser population and the corresponding need to individualize treatment appropriate to their own clientele. Recidivism outcome studies are reviewed from the perspective of their contribution to questions of which sorts of treatments appear to be effective with which populations, rather than whether they do or do not support a generalized conclusion regarding treatment efficacy. Studies addressing the scope of deviance, nonsexual antisocial behavior, treatment outcome, prediction of compliance, and the question of coerced treatment are examined